A halofuginone electrochemical sensor based on a molecularly imprinted polypyrrole coated glassy carbon electrode1. Issue 19 (7th October 2015) - Radi, Abd-Elgawad; Abd-Elaziz, Ismael
<x xml:space="preserve">Abstract</x> In this work, a novel and selective polypyrrole (PPy) electropolymerized molecularly imprinted electrochemical sensor (PPy-MIP) for halofuginone (HFG) determination was developed.